2020
DOI: 10.3390/educsci10100263
|View full text |Cite
|
Sign up to set email alerts
|

The Role of External and Internal Team Coaches in Teacher Design Teams. A Mixed Methods Study

Abstract: Teacher design teams (TDTs) are increasingly used as a means for teacher professional development. It has been posited that for teacher learning to occur, TDTs need support from team coaches. These coaches are either external experts or peer teachers that guide the team from within. The current literature is in debate on whether external or internal coaches are most effective in supporting TDTs. In this study, we, therefore, examine whether these coach types differ in how they fulfil their role. We additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…A chairperson or group facilitator who is not afraid to introduce structure, halt endless discussions and make decisions in support of the group's objective(s) [26,54,71]. In line with research by Compen and Schelfhout [83], we found that external process coaches were not better positioned to adopt such a role and establish the PLC's objectives than was an internal process coach. When participants are acquainted and the PLC's objectives are not too complex (requiring considerable external input), the role of the process coach can easily be adopted by a primus inter pares.…”
Section: The Role Of the Process Coachsupporting
confidence: 71%
See 2 more Smart Citations
“…A chairperson or group facilitator who is not afraid to introduce structure, halt endless discussions and make decisions in support of the group's objective(s) [26,54,71]. In line with research by Compen and Schelfhout [83], we found that external process coaches were not better positioned to adopt such a role and establish the PLC's objectives than was an internal process coach. When participants are acquainted and the PLC's objectives are not too complex (requiring considerable external input), the role of the process coach can easily be adopted by a primus inter pares.…”
Section: The Role Of the Process Coachsupporting
confidence: 71%
“…Collaborative activities and the social support found therein can increase job enthusiasm, satisfaction and motivation [44] and, the confidence one has in his or her job [7]. Participation in PLCs-and similar forms of group coaching-is, furthermore, believed to facilitate (teacher) professional learning [13,26,27,32,34,81] and render concrete tools or material [82,83]. Notwithstanding several of these findings were derived from teacher and within-school PLC set-ups, we hypothesize similar tendencies using principal networked PLCs.…”
Section: Collective or Networked Learning And Professional Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, Vangrieken et al (2017) state that teacher communities are conducive for sustainable improvements in teaching practices and can have an (indirect) positive impact on teachers’ professional development and student achievement (Hord, 2004; Lomos et al, 2011; Stoll et al, 2006). Furthermore, Compen and Schelfhout (2020) state that the enhanced ownership emerging from commitment in collaborative discourse is suggested to positively impact teachers’ enthusiasm to implement the curricular changes.…”
Section: Understanding Professional Learning Communitiesmentioning
confidence: 99%
“…As indicated in the definition, collaboration takes place between two or more professionals. Usually two teachers are involved (i.e., two (general) teachers, or a (general) teacher and a special education teacher), but other ways of collaboration are equally possible (e.g., between three or more professionals, with a student teacher, a mentor during field experiences, a teacher trainer, a child caretaker, a paramedic, or even a larger group of teachers with specific development goals [25]).…”
Section: Collaborative Learning Through Team Teachingmentioning
confidence: 99%